2020
DOI: 10.1101/2020.10.07.307991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacological inhibition of the ALK axis elicits therapeutic potential in Consensus Molecular Subtype 1 colon cancer patients

Abstract: In the last years, several efforts have been made to classify colorectal cancer (CRC) into well-defined molecular subgroups, representing the intrinsic inter-patient heterogeneity, known as Consensus Molecular Subtypes (CMSs). In this work, we performed a meta-analysis of 1700 CRC patients stratified into four CMSs. We identified a negative correlation between a high level of anaplastic lymphoma kinase (ALK) expression and relapse-free survival, exclusively in CMS1 subtype. Stemming from this observation, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…Accordingly, we were able to document that CZB treatment has an impact on the mass density, which represents an important marker characterizing cancer cell treatment. We speculate that the possible mechanism responsible for the increased spheroid mass density may be related to the enhanced cell-cell adhesion, as previously reported [27]. Indeed, we found that CZB treated cells displayed increased e-cadherin production, with consequent improved tight-junction organization.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Accordingly, we were able to document that CZB treatment has an impact on the mass density, which represents an important marker characterizing cancer cell treatment. We speculate that the possible mechanism responsible for the increased spheroid mass density may be related to the enhanced cell-cell adhesion, as previously reported [27]. Indeed, we found that CZB treated cells displayed increased e-cadherin production, with consequent improved tight-junction organization.…”
Section: Discussionsupporting
confidence: 85%
“…We found that in live samples CZB treatment significantly decreases weight and size ( Fig 2B and 2C ) at concentrations of 250 and 500 nM, compared to CTRL. This is in line with an antiproliferative activity of the inhibitor [ 27 ]. On the other hand, under the same treatments, mass density displays an opposing result, with a significant increase in the density of the spheroids’ bulk ( Fig 2A ).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations